2000
DOI: 10.1073/pnas.97.4.1456
|View full text |Cite
|
Sign up to set email alerts
|

Human aspartic protease memapsin 2 cleaves the β-secretase site of β-amyloid precursor protein

Abstract: The cDNAs of two new human membrane-associated aspartic proteases, memapsin 1 and memapsin 2, have been cloned and sequenced. The deduced amino acid sequences show that each contains the typical pre, pro, and aspartic protease regions, but each also has a C-terminal extension of over 80 residues, which includes a single transmembrane domain and a C-terminal cytosolic domain. Memapsin 2 mRNA is abundant in human brain. The protease domain of memapsin 2 cDNA was expressed in Escherichia coli and was purified. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
636
2
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 749 publications
(667 citation statements)
references
References 16 publications
24
636
2
5
Order By: Relevance
“…Up to now, studies of BACE have concentrated on its structure [4,45], trafficking [11,16,[46][47][48][49][50], and specific inhibition [10], but how its activity is regulated remains largely unclear. In this study, we demonstrated that BACE activity both in vitro and in vivo could be efficiently regulated by RTKs, and the regulation of BACE activity led to alterations of subsequent Aβ production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, studies of BACE have concentrated on its structure [4,45], trafficking [11,16,[46][47][48][49][50], and specific inhibition [10], but how its activity is regulated remains largely unclear. In this study, we demonstrated that BACE activity both in vitro and in vivo could be efficiently regulated by RTKs, and the regulation of BACE activity led to alterations of subsequent Aβ production.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, β-secretase is considered the initial and rate-limiting enzyme during this process. β-site APP cleavage enzyme (BACE), a type I integral membrane aspartic protease, was identified as the main β-secretase [3][4][5][6][7]. As formation of senile plaques could not be detected in BACE-deficient mice [8,9], BACE has attracted major attentions in AD research during recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, BACE1 (also: b-secretase 1 or memapsin 2) was identified as a b-site APP-cleaving enzyme, [7][8][9][10][11] and, 2 years later, confirmed as the major b-secretase in vivo. 12 BACE1 initiates the amyloidogenic pathway of APP processing.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…Expression cloning or biochemical purification led to the identification of a unique b-secretase enzyme (Sinha et al 1999;Vassar et al 1999;Yan et al 1999;Hussain et al 2000;Lin et al 2000). Although many different names were originally used to describe this activity, such as memapsin, aspartyl protease 2, or BACE1 (b-site APP cleaving enzyme-1), BACE1 is now the generally accepted term for the enzyme harboring b-secretase activity.…”
mentioning
confidence: 99%